2020
DOI: 10.22270/jddt.v10i6-s.4403
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine-Fentanyl vs Ropivacaine-Fentanyl: Evaluation of two Spinal Anesthesia Protocols for Emergency Cesarean Section

Abstract: Objective: Evaluation of the hemodynamic, respiratory and fetal side effects of two protocols for spinal anesthesia (P1: bupivacaine-fentanyl; P2: ropivacaine-fentanyl). Material and Method: Prospective pseudo-randomized study comparing two spinal anesthesia protocols for emergency cesarean section conducted in the operating room of the regional hospital center of Saint Louis in Senegal. Study duration was 4 months. We studied, age, indication for Caesarean section, medical and surgical history, P1 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…On the basis of these findings, the authors concluded that ropivacaine is a better choice due to little influence on the hemodynamics and shorter duration of sensory block and motor block which are useful for the recovery and also safe to the patients. Similar findings were also reported by the authors such as Diedhiou et al, 18 and Memon and Pathak. In our study, the incidence of nausea and vomiting as well as hypotension and bradycardia was seen in a greater number of patients in Group BF as compared to Group RF; however, the overall incidence of side effects was found to be comparable in both the groups.…”
Section: Discussionsupporting
confidence: 91%
“…On the basis of these findings, the authors concluded that ropivacaine is a better choice due to little influence on the hemodynamics and shorter duration of sensory block and motor block which are useful for the recovery and also safe to the patients. Similar findings were also reported by the authors such as Diedhiou et al, 18 and Memon and Pathak. In our study, the incidence of nausea and vomiting as well as hypotension and bradycardia was seen in a greater number of patients in Group BF as compared to Group RF; however, the overall incidence of side effects was found to be comparable in both the groups.…”
Section: Discussionsupporting
confidence: 91%